On Reporting Attitudes: an Analysis of Desire Reports and their Reading-Establishing Scenarios - Pross, Tillmann (Proceedings of the Amsterdam Colloquium, 2015)
I argue that conventional wisdom about attitude reports lumps together theorizing about the attitudes themselves with theorizing about the meaning of attitude reports. Instead of conflating these, I propose to treat them as distinct (although obviously related) topics. A central reason for this separation is the distinction between anaphoric constructions that are internally about the same object and anaphoric constructions that are externally about the same object. Anaphoric constructions that are internally about the same object reveal the structure of the attitudes themselves– e.g. that desires are parasitic on beliefs– whereas anaphoric constructions which are externally about the same object make explicit the structure of attitude reports. I correlate the distinction between the attitudes themselves and attitude reports with the asymmetry between the first- and third-person perspective on attitudes. On the basis of this asymmetry, I propose a semantics of desire reports according to which a desire report like Adrian wants to buy a jacket like Malte’s is not ambiguous between different readings. Conventional wisdom readings are reconstructed as a third person’s pragmatic strategies for justifying the truth of an attitude ascription. I conclude with an outlook on the transfer of the analysis proposed to reports involving other non-doxastic predicates like wish or hope and reports involving doxastic predicates such as believe.